Editorial: the impact of steatosis on liver stiffness quantification is minimal. Issue 10 (19th April 2018) - Hassan, A.; Tapper, E. B.
Abstract : Linked Content This article is linked to Karlas et al papers. To view these articles visithttps://doi.org/10.1111/apt.14529 andhttps://doi.org/10.1111/apt.14632 .